2019
DOI: 10.1177/0340035219886610
|View full text |Cite
|
Sign up to set email alerts
|

National and international trends in library and information science research: A comparative review of the literature

Abstract: The study is an attempt to understand the trends in LIS research by analyzing published literature on the topic. The study identifies and analyses 39 research papers on LIS research trends in various countries, three papers on LIS research trends in regional countries and 13 papers on LIS research trends with an international perspective. The findings of the study reveal that there is a similarity among various countries as far as the LIS research topics are concerned but with a different focus at different pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
1
14
0
1
Order By: Relevance
“…Although there are a number of factors which influence students to choose a subject to research such as funding, supervisors' knowledge on the subject, student's preference, weak research skills (Ndenje-Sichalwe & Elia, 2021, Dora & Kumar, 2020, Mutula, 2011, researchers' supervision experience, majority of postgraduate students who have permanent employment are largely influenced by the employment status, nature of work, working environment and workstation. On the other hand, non-employed, fresh from school graduates from lower levels who joins postgraduate LIS education prefer choosing topic of their interest with assistance from supervisors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are a number of factors which influence students to choose a subject to research such as funding, supervisors' knowledge on the subject, student's preference, weak research skills (Ndenje-Sichalwe & Elia, 2021, Dora & Kumar, 2020, Mutula, 2011, researchers' supervision experience, majority of postgraduate students who have permanent employment are largely influenced by the employment status, nature of work, working environment and workstation. On the other hand, non-employed, fresh from school graduates from lower levels who joins postgraduate LIS education prefer choosing topic of their interest with assistance from supervisors.…”
Section: Discussionmentioning
confidence: 99%
“…Rochester (2016) conducted a study in Australia between 1985 and 1994 and revealed information seeking, library history, information storage and retrieval and scientific and professional communication were mostly topics researched while methodology, information dissemination and cataloguing were not researched. Dora and Kumar (2020) observed information technology, information retrieval, bibliometrics, libraries, scientific communication to be widely researched. Prebor (2007) found topics highly researched were information industry economics and management, social aspects of information, information seeking and data organisation and retrieval.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Vairākus šādus pētījumus veikuši divi Tamperes Universitātes profesori K. Jervelins (Järvelin) un P. Vakari (Vakkari) (Järvelin, & Vakkari, 1990;Järvelin, & Vakkari, 1993;Järvelin, & Vakkari, 2022). Plašu apkopojošu pētījumu par pētniecības tendencēm gan atsevišķās valstīs, gan reģionos un starptautiskā kontekstā veikuši divi indiešu pētnieki M. Dora (Dora) un A. Kumars (Kumar) (Dora & Kumar 2020).…”
Section: Aktuālie Pētniecības Virzieni Bibliotēkzinātnē Un Informācij...unclassified
“…In the second decade of the 21st century, the UX movement gained momentum (Augusto et al, 2018;Bowler et al, 2011;Dora and Kumar, 2020;Luca and Ulyannikova, 2020;Miller, 2019). During this time, influenced by UX, PD began to take on more aspects of action research by promoting a reflective process, design-based thinking, and the collaborative solving of real-world problems directly affecting participants (Atkins and Wallace, 2012;Darby, 2017;Singh, 2020;Wilson, 2013).…”
Section: Participatory Designmentioning
confidence: 99%